Photoreceptor Guanylate Cyclase (GUCY2D) Mutations Cause Retinal Dystrophies by Severe Malfunction of Ca2+-Dependent Cyclic GMP Synthesis - Wimberg, Hanna; Lev, Dorit; Yosovich, Keren; Namburi, Prasanthi; Banin, Eyal; Sharon, Dror; Koch, Karl-Wilhelm (Frontiers in Molecular Neuroscience, 2018)
Over 100 mutations in GUCY2D that encodes the photoreceptor guanylate cyclase GC-E are known to cause two major diseases: autosomal recessive Leber congenital amaurosis (arLCA) or autosomal dominant cone-rod dystrophy (adCRD) with a poorly understood mechanism at the molecular level in most cases. Only few mutations were further characterized for their enzymatic and molecular properties. GC-E activity is under control of neuronal Ca2+-sensor proteins, which is often a possible route to dysfunction. We investigated five recently-identified GC-E mutants that have been reported in patients suffering from arLCA (1 large family) and adCRD/maculopathy (4 families). Microsatellite analysis revealed that one of the mutations, c.2538G>C (p.K846N), occurred de-novo. To better understand the mechanism by which mutations that are located in different GC-E domains develop different phenotypes, we investigated the molecular consequences of these mutations by expressing wildtype and mutant GC-E variants in HEK293 cells. Analyzing their general enzymatic behavior, their regulation by Ca2+ sensor proteins and retinal degeneration protein 3 (RD3) dimerization domain mutants (p.E841K and p.K846N) showed a shift in Ca2+-sensitive regulation by guanylate cyclase-activating proteins (GCAPs). Mutations in the cyclase catalytic domain led to a loss of enzyme function in the mutant p.P873R, but not in p.V902L. Instead, the p.V902L mutation increased the guanylate cyclase activity more than 20-fold showing a high GCAP independent activity and leading to a constitutively active mutant. This is the first mutation to be described affecting the GC-E catalytic core in a complete opposite way.